Remote sensing for greenhouse detection from stereo pairs of WorldView-2 satellite - M.A. Aguilar; M.A. Montalbán; M.M. Saldaña; F.J. Aguilar; I. Fernández; A.M. García-Lorca (Revista de Teledetección)
The successful launch of the first very high resolution (VHR) satellites capable of capturing panchromatic imagery of the land surface with ground sample distance even lower than 1 m (e.g. IKONOS in 1999 or QuickBird in 2001) marked the beginning of a wholly new age in remote sensing. On January 4, 2010, images of WorldView-2 were placed on the market. Possibly it is the most sophisticated commercial VHR satellite currently orbiting the Earth and the exploitation of its data poses a challenge to researchers worldwide. Moreover, the practice of under plastic agriculture had a great development in the Mediterranean area during the past 60 years, especially in Almeria, acting as a key economic driver in the area. The goal of this work is the automatic greenhouse mapping by using Object Based Image Analysis (OBIA). The required input data will be a pan-sharpened orthoimage and a normalized digital surface model (nDSM) for objects, both products generated from a WorldView-2 stereo pair. The attained results show that the very high resolution 8-band multispectral and the nDSM data improve the greenhouses automatic detection. In this way, overall accuracies higher than 90% can be achieved.